2021
DOI: 10.1002/dev.22168
|View full text |Cite
|
Sign up to set email alerts
|

Paternal biopsychosocial resilience in triadic interactions among African American/Black families exposed to trauma and socioeconomic adversity

Abstract: Fathers have a distinct and unique effect on child development, but little is known about fathering beyond White or majority White families. The current study includes African American/Black biological fathers (N = 88) and their two‐year‐old children. Fathers reported low incomes and high rates of depression and posttraumatic stress disorder (PTSD). Parenting behaviors were observed in high‐stress and low‐stress triadic contexts. In the high‐stress condition, we assessed paternal responses to children's bids a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 103 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…In a related study focusing on paternal mental health and RSA, Bocknek et al. (2021) found in a study of African American fathers that those with higher RSA and PTSD symptoms showed greater responsiveness to their children following a stressor, while those with lower RSA were less responsive. The findings help shed light on individual differences in fathers’ psychobiology that helps buffer against adverse parenting practices that could otherwise accompany PTSD, which may represent an intriguing possibility for future intervention‐oriented research under conditions of adversity.…”
mentioning
confidence: 99%
“…In a related study focusing on paternal mental health and RSA, Bocknek et al. (2021) found in a study of African American fathers that those with higher RSA and PTSD symptoms showed greater responsiveness to their children following a stressor, while those with lower RSA were less responsive. The findings help shed light on individual differences in fathers’ psychobiology that helps buffer against adverse parenting practices that could otherwise accompany PTSD, which may represent an intriguing possibility for future intervention‐oriented research under conditions of adversity.…”
mentioning
confidence: 99%